Functional preservation and variation in the cone opsin genes of nocturnal tarsiers. (5th April 2017) - Moritz, Gillian L.; Ong, Perry S.; Perry, George H.; Dominy, Nathaniel J.
Abstract : The short-wavelength sensitive (S-) opsin gene OPN1SW is pseudogenized in some nocturnal primates and retained in others, enabling dichromatic colour vision. Debate on the functional significance of this variation has focused on dark conditions, yet many nocturnal species initiate activity under dim (mesopic) light levels that can support colour vision. Tarsiers are nocturnal, twilight-active primates and exemplary visual predators; they also express different colour vision phenotypes, raising the possibility of discrete adaptations to mesopic conditions. To explore this premise, we conducted a field study in two stages. First, to estimate the level of functional constraint on colour vision, we sequenced OPN1SW in 12 wild-caught Philippine tarsiers ( Tarsius syrichta ). Second, to explore whether the dichromatic visual systems of Philippine and Bornean ( Tarsius bancanus ) tarsiers—which express alternate versions of the medium/long-wavelength sensitive (M/L-) opsin gene OPN1MW / OPN1LW —confer differential advantages specific to their respective habitats, we used twilight and moonlight conditions to model the visual contrasts of invertebrate prey. We detected a signature of purifying selection for OPN1SW, indicating that colour vision confers an adaptive advantage to tarsiers. However, this advantage extends to a relatively small proportion of prey–background contrasts, and mostly brown arthropod prey amid leaf litter. We also found that the colour vision of T. bancanus is advantageous for discriminating prey under twilight that is enriched in shorter (bluer) wavelengths, a plausible idiosyncrasy of understorey habitats in Borneo. This article is part of the themed issue 'Vision in dim light'.